A influência dos aspectos psicossociais no impacto da condição bucal na qualidade de vida de adultos de uma cidade de médio porte do sul do Brasil - Ferreira, Denise Carvalho (Universidade do Vale do Rio dos Sinos, 2015)
This master's thesis in Public Health entitled "The influence of psychosocial factors on the impact of the oral health related quality of life of Brazilian adultsl", is justified by the need to better understand the relationship between psychosocial aspects and the perception of oral health on quality of life. Taking into account the influence of psychosocial factors may contribute to the development of effective public health policies in order to minimize the negative impact of oral health problems in people's lives. The dissertation consists of the research project, field report and scientific article. The theoretical and methodological aspects of the research question are described in the research project. The field report describes all aspects of data collections and details of field work logistics. The scientific article discuss the the main findings which showed that prevalences of the Oral Health Impact Profile were found in women, older, less educated and lower income people, in smokers and in those with poor self-rated oral health. All, except spirituality, psychosocial variables were associated with the worst impact of oral health on quality of life. The findings suggest the need of taking into account both psychosocial and oral health related aspects so that negative impact that oral health has on the quality of life can be minimized.
Keywords: OHIP; Saúde bucal; Qualidade de vida; Aspectos psicossociais; Oral health; Quality of life; Psychosocial aspects; ACCNPQ::Ciências da Saúde::Saúde Coletiva